-3.6-7.2=12.7-6.1b

Simple and best practice solution for -3.6-7.2=12.7-6.1b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3.6-7.2=12.7-6.1b equation:


Simplifying
-3.6 + -7.2 = 12.7 + -6.1b

Combine like terms: -3.6 + -7.2 = -10.8
-10.8 = 12.7 + -6.1b

Solving
-10.8 = 12.7 + -6.1b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '6.1b' to each side of the equation.
-10.8 + 6.1b = 12.7 + -6.1b + 6.1b

Combine like terms: -6.1b + 6.1b = 0.0
-10.8 + 6.1b = 12.7 + 0.0
-10.8 + 6.1b = 12.7

Add '10.8' to each side of the equation.
-10.8 + 10.8 + 6.1b = 12.7 + 10.8

Combine like terms: -10.8 + 10.8 = 0.0
0.0 + 6.1b = 12.7 + 10.8
6.1b = 12.7 + 10.8

Combine like terms: 12.7 + 10.8 = 23.5
6.1b = 23.5

Divide each side by '6.1'.
b = 3.852459016

Simplifying
b = 3.852459016

See similar equations:

| (4x-2)(4x-2)+(5x)(5x)= | | 10x-4-6x=5x-7 | | (-10)+4=-2(-10)+-6 | | 2a+8=4a+16 | | 5(4x-4)-9=-31 | | 216=8(-5r-3) | | (3x+y*1)=(7*2x-3y) | | 29.95=42-sqrt(0.001x+2) | | (x^2+2xy)dx+xdy=0 | | 5w-6=60 | | 18=9x+4-2x | | (3+2x)=0.5x+1 | | 7x+10=4x-16 | | 3X=6-3 | | -19=v/10 | | 3x+3x-7=47 | | 2x[2+(5+2)]= | | ln(9x)=2ln(2x) | | 5(4x-4)-9=31 | | X-4y+15=0 | | -3x+4x-10=15x+1 | | 3n-2m=mn+4 | | X+7x=-24 | | 5y^2+40y=325 | | 5(3x-7)-3(x+2)-19x= | | 3(x-2)+(-3)=4(x+1) | | r(2x+3)=0.5x+1 | | b^2=-2+3b | | 20x+12y=344 | | 2(5z-1)-5(z+9)=2(z+1) | | 18-3x=2+2x | | 9n^2=-1 |

Equations solver categories